The State of the World's Genetic Resources for Food and Agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
FAO. 1998. 510 pp.ISBN 92 5 104073 7.$55.00 , Euro 53.10FAO Plant Production and Protection Division,Viale delle Terme di Caracalla, 00100 Rome, Italy.Fax: +39 06 57 05 55 33Email: icppgr@fao.org